Parallel paired electrolysis of green oxidizing agents by the combination of a gas diffusion cathode and boron-doped diamond anode - Hamm, Christin M.; Schneider, Selina; Hild, Stefanie; Neuber, Rieke; Matthée, Thorsten; Krümberg, Jens; Stöckl, Markus; Mangold, Klaus-Michael; Kintrup, Jürgen (Frontiers in Catalysis, 2024)
The generation of "green" oxidizing agents by electrochemical synthesis opens the field for a sustainable, on demand and on-site production, which is often based on non-critical starting materials. In this study, electrosyntheses were carried out on different cathode and anode materials. In half-cell experiments, the cathodic synthesis of peroxyacetic acid (PAA) was investigated on gas diffusion electrodes (GDE), reaching 22.6 mmol L -1 of PAA with a current efficiency (CE) 7.4%. Moreover, peroxodicarbonate (PODIC ® ) was produced anodically on boron doped diamond (BDD) electrodes with concentrations as high as 42.7 mmol L -1 PODIC ® and a CE of 30.3%. Both cathodic and anodic processes were individually examined and improved. Finally, the half-cell reactions were combined as a proof-of-concept in a parallel paired electrolysis cell for the first time to achieve an increased over all current efficiency.